2022
DOI: 10.3389/fendo.2022.925119
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic model for predicting hyperuricemia based on alterations of the gut microbiome in individuals with different serum uric acid levels

Abstract: BackgroundWe aimed to assess the differences in the gut microbiome among participants with different uric acid levels (hyperuricemia [HUA] patients, low serum uric acid [LSU] patients, and controls with normal levels) and to develop a model to predict HUA based on microbial biomarkers.MethodsWe sequenced the V3-V4 variable region of the 16S rDNA gene in 168 fecal samples from HUA patients (n=50), LSU patients (n=61), and controls (n=57). We then analyzed the differences in the gut microbiome between these grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…[ 74 , 75 ]. In the study of Liang et al [ 76 ], the abundance of Ruminococcus in the intestinal flora of HUA patients was significantly decreased and was considered a microbiological marker of HUA, while in the present study, this bacterium could be upregulated by MOS.…”
Section: Discussioncontrasting
confidence: 40%
“…[ 74 , 75 ]. In the study of Liang et al [ 76 ], the abundance of Ruminococcus in the intestinal flora of HUA patients was significantly decreased and was considered a microbiological marker of HUA, while in the present study, this bacterium could be upregulated by MOS.…”
Section: Discussioncontrasting
confidence: 40%
“…And the increase of Bacteroides has also been proved to be positively correlated with uric acid content [46] . In addition, some studies have also confirmed that the increase of Prevotella and Bacteroides is common in the intestines of hyperuricemic animals [47][48] . And Prevotella stimulates dendritic cells (DC) to release IL-1β, IL-6, etc., so we speculate that the imbalance of Prevotella was related to the occurrence of intestinal inflammation [45] .…”
Section: Discussionmentioning
confidence: 84%
“…Future research aims to delve deeper into understanding the gut microbiota and its metabolic products, airway microbiota and their metabolites, and to develop suitable bioinformatics and machine learning models. These models are intended to predict and assess various gut-lung axis diseases and health statuses, leading to the development of personalized prevention and treatment strategies ( Zheng et al., 2020 ; Zheng et al., 2023 ; Liang et al., 2022 ). Recent discoveries indicate significant differences in the gut microbiota of lung cancer patients compared to their lung microbiome communities.…”
Section: Discussionmentioning
confidence: 99%